Life cycle of cosmic-ray electrons in the intracluster medium - Vazza, F.; Wittor, D.; Di Federico, L.; Brüggen, M.; Brienza, M.; Brunetti, G.; Brighenti, F.; Pasini, T. (Astronomy and astrophysics (Berlin), 2023)
We simulate the evolution of relativistic eletrons injected into the medium of a small galaxy cluster by a central radio galaxy, studying how the initial jet power affects the dispersal and the emission properties of radio plasma. By coupling passive tracer particles to adaptive-mesh cosmological magnetohydrodynamic (MHD) simulations, we study how cosmic-ray electrons are dispersed as a function of the input jet power. We also investigate how the latter affects the thermal and non-thermal properties of the intracluster medium, with differences discernible up to about one Gyr after the start of the jet. We evolved the energy spectra of cosmic-ray electrons, subject to energy losses that are dominated by synchrotron and inverse Compton emission as well as energy gains via re-acceleration by shock waves and turbulence. We find that in the absence of major mergers, the amount of re-acceleration experienced by cosmic-ray electrons is not enough to produce long-lived detectable radio emissions. However, for all simulations, the role of re-acceleration processes is crucial to maintaining a significant and volume-filling reservoir of fossil electrons ( γ ∼ 10 3 ) for at least one Gyr after the first injection by jets. This is important in attempting to establish plausible explanations of recent discoveries of cluster-wide emission and other radio phenomena in galaxy clusters.